Snow White with the red hair. 2 - Akiduki, Sorata (Shojo beat manga., 2019)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! Unwilling to become the prince's possession, she seeks shelter in the woods of the neighboring kingdom, where she gains an unlikely ally--the prince of that kingdom! He rescues her from her plight, and thus begins the love story between a lovestruck prince and an unusual herbalist... Shirayuki begins her duties as a court herbalist apprentice, but her mentor is a bit odd. He's quiet, shy, moody and...a child? Her first official duty is to quell an illness going around one of the forts that house Clarines soldiers. Will she be able to discover the cause of the outbreak in time?"--Provided by publisher.